A 3D Parametric Venusian Bow Shock Model with the Effects of Mach Number and Interplanetary Magnetic Field - Ming Wang; Qi Xu; Lianghai Xie; Lei Li; Xiaojun Xu (The Astronomical Journal, 2024)
Using global magnetohydrodynamics simulations, we have developed a three-dimensional parametric model for the Venusian bow shock based on a generalized conic section function defined by six parameters, with the effects of the solar wind magnetosonic Mach number ( M _MS ) and the interplanetary magnetic field (IMF) involved. The parametric model’s results reveal the following findings: (1) The size of the Venusian bow shock is primarily determined by M _MS . An increase in M _MS results in the bow shock moving closer to Venus and a reduction in its flaring angle. (2) Both the subsolar standoff distance and the bow shock’s flaring angle increase with the strength of the IMF components that are perpendicular to the solar wind flow direction ( B _Y and B _Z in the Venus-centered solar orbital coordinate system), whereas the parallel IMF component ( B _X ) has a limited impact on the subsolar standoff distance but affects the flaring angle. (3) The cross section of the bow shock is elongated in the direction perpendicular to the IMF on the Y – Z plane, and the elongation degree is enhanced with increasing intensities of B _Y and B _Z . (4) The quasi-parallel bow shock locates closer to the planet as compared to the quasi-perpendicular bow shock. These findings are in alignment with prior empirical and theoretical models. The influences of M _MS and IMF on the bow shock’s position and geometry are attributed to the propagation of fast magnetosonic waves, showing the nature of the formation of a collisionless bow shock under the interaction of magnetized flow with an atmospheric object.